PERFORMA PRODUKSI DAN KUALITAS TELUR AYAM KETARRAS PADA SISTEM PEMELIHARAAN KANDANG BATERAI DAN UMBARAN - Kususiyah Kususiyah; Desia Kaharuddin; Edi Soetrisno; Muhammad Dani (Wahana Peternakan, 2023)
The aim of the study was to evaluate egg production performance and egg quality of Ketarras chickens in  battery and umbaran rearing system. The study used 100 female Ketarras chickens aged 20 weeks; divided into 2 groups of maintenance systems, namely 50 in the battery cage and 50 in the umbaran rearing. The research was conducted at the Commercial Zone and Animal Laboratory (CZAL) Department of Animal Husbandry, Faculty of Agriculture, University of Bengkulu. Variables of production performance include: feed consumption, egg weight, percentage of egg production, egg mass production and feed conversion, while egg quality variables include: sample egg weight, egg index, yolk color, yolk weight, albumen weight, egg shell weight and shell thickness egg. Sampling for observation of egg quality was 100 eggs in each rearing system. Production performance data is discussed descriptively, while egg quality data is analyzed using the t test. The results of the evaluation of production performance showed that feed consumption and feed conversion in battery cages were lower with egg weight, egg production percentage and egg mass production being higher than in umbaran rearing system. The results of the t test showed that the rearing system had no significant effect (t count<t table) on all egg quality variables. It can be concluded that the egg production performance of Ketarras chickens in battery cages is better than in umbaran rearing system without any difference in egg quality. Keyword : Ketarras Chicken, Rearing System, Performance, Egg Quality